2014
DOI: 10.1016/j.biochi.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Plant phosphoinositide-dependent phospholipases C: Variations around a canonical theme

Abstract: Phosphoinositide-specific phospholipase C (PI-PLC) cleaves, in a Ca(2+)-dependent manner, phosphatidylinositol-4,5-bisphosphate (PI-4,5-P2) into diacylglycerol (DAG) and inositol triphosphate (IP3). PI-PLCs are multidomain proteins that are structurally related to the PI-PLCζs, the simplest animal PI-PLCs. Like these animal counterparts, they are only composed of EF-hand, X/Y and C2 domains. However, plant PI-PLCs do not have a conventional EF-hand domain since they are often truncated, while some PI-PLCs have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
82
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 193 publications
(280 reference statements)
1
82
0
1
Order By: Relevance
“…During the preparation of this manuscript, a comprehensive review was published, 37 describing different features of plant PI-PLCs including expression patterns of different isoforms in conjunction with biotic and abiotic challenges in different plant species. Of the various isoforms known, the PLC2 isoform, used in this study, although constitutively expressed in Arabidopsis, is not significantly induced by low temperature or biotic stress conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the preparation of this manuscript, a comprehensive review was published, 37 describing different features of plant PI-PLCs including expression patterns of different isoforms in conjunction with biotic and abiotic challenges in different plant species. Of the various isoforms known, the PLC2 isoform, used in this study, although constitutively expressed in Arabidopsis, is not significantly induced by low temperature or biotic stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while the same isoform is shown to be upregulated by cold and downregulated by biotic stress in wheat, its expression follows an opposite trend in rice. 37 What is more, in B. napus, unlike Arabidopsis, this isoform is significantly induced by cold, 12 implying the possibility of species-specific expression regulation.…”
Section: Discussionmentioning
confidence: 99%
“…These second messengers then activate protein kinase C (PKC) and the ER-localised IP 3 receptor, respectively, in animal cells [1,2]. However, although the PI-PLC signaling cascade is present in plants [5][6][7], genes encoding PKC and the IP 3 receptor have not been found in terrestrial plant genomes, suggesting differences in second messenger systems between animals and plants. To date, the genomes of a variety of unicellular and multicellular algae have been sequenced [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] as shown in (Table 1).…”
mentioning
confidence: 99%
“…To date, PA and IP 6 are thought to act as major second messengers in plant cells [7,54], although the function of IP 3 as a second messenger in plants has not been ruled out [42,47]. For instance, Munnik and Vermeer [54] have proposed that IP 6 , which is rapidly converted from IP 3 , is a major second messenger involved in abscisic acid-dependent inhibition of stomatal opening.…”
mentioning
confidence: 99%
“…This lipid can be phosphorylated into phosphatidic acid by diacylglycerol-kinases (DGK). 6 The PI-PLC/DGK pathway is active in nonstimulated Arabidopsis cells or plants. 7,8 We recently showed that this basal activity negatively regulated the expression of DREB2A, DREB2B, DREB2C, DREB2E, and DREB2H genes.…”
mentioning
confidence: 99%